Health Care Service Model for the Bed Bound Elder by Community Participation, Sungaikolok Subdistrict, Narathiwat - มะหะหมัด, เพ็ญนภา (Princess of Naradhiwas University Journal, 2018)
The aim of this participatory action research was to study a community participation health care service model for the bed bound elder in Sungaikolok Subdistrict of Narathiwat, Southern Thailand. The sample consisted of 64 stakeholders. The data collection tools were a questionnaire for in-depth interview and a questionnaire for satisfaction that were both tested for content validity by 3 experts, and tested for reliability with Cronbach’s alpha coefficient, yielding values of 0.71 and 0.75, respectively. Data were analyzed using percentage, mean, and content analysis. The research results showed the following. The problems of the bed bound elder were: 1) multi-morbidity, 2) lack of psychological support, 3) insufficient economical means, and 4) weak social environment. Needs of health care service for the bed bound elder were: 1) home health care, 2) continuous home care and coaching, 3) adjusting social environmentand budget, and 4) quick, safe, and easy access to health care services. The health care service model for thebed bound elder was developed in community with participation of volunteers, caregivers, and network toenhance quality of life of stakeholders. The evaluation of satisfaction showed that the stakeholders were satisfiedwith developed health care service model at highest score. ( =4.78, S.D.=0.19; =4.42, S.D.=0.20)